2017
DOI: 10.1111/prd.12149
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of pathologic peri‐implant pockets

Abstract: Peri-implant and periodontal pockets share a number of anatomical features but also have distinct differences. These differences make peri-implant pockets more susceptible to trauma and infection than periodontal pockets. Inadequate maintenance can lead to infections (defined as peri-implant mucositis and peri-implantitis) within peri-implant pockets. These infections are recognized as inflammatory diseases, which ultimately lead to the loss of supporting bone. Diagnostic and treatment methods conventionally u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
144
0
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(164 citation statements)
references
References 77 publications
3
144
0
17
Order By: Relevance
“…The elimination of biofilms on implant surfaces is one of the most important factors to promote proper healing as any residual pathogens may be eliminated by the host's immune system . In this study, periodontal pathogens were found, which may play an important role in the pathogenesis of peri‐implantitis.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The elimination of biofilms on implant surfaces is one of the most important factors to promote proper healing as any residual pathogens may be eliminated by the host's immune system . In this study, periodontal pathogens were found, which may play an important role in the pathogenesis of peri‐implantitis.…”
Section: Discussionmentioning
confidence: 76%
“…Non‐surgical mechanical debridement therapy should always be performed prior to other treatments for peri‐implantitis, as dentists can monitor the soft tissue healing process as well as guide patients to achieve effective oral hygiene . However, the prognosis of the treatment for peri‐implantitis remains poor .…”
Section: Discussionmentioning
confidence: 99%
“…However, it was concluded that the available evidence did not allow any recommendations for peri‐implantitis treatment. Nevertheless, surgical peri‐implantitis treatment has been shown to be more effective when compared to non‐surgical treatment, even though the evidence available does not allow strong conclusions due to the limited number and low methodological quality of the studies . Moreover, there is still no clear evidence as to the best mechanical approach, even though air abrasive devices might present better surface decontamination …”
Section: Discussionmentioning
confidence: 99%
“…In an advanced stage of the disease, with the constant and increased presence of dangerous bacterial products and consequent immune inflammatory biological response, elimination of the biofilm from the implant surface is the prime process to interrupt disease progression . However, depending on the bone loss extension, complete eradication of biofilm attached on dental implants is not easy, mainly in the apical region because peri‐implant pocket becomes deeper as the bone resorbs. Nowadays, focus on peri‐implantitis treatment requires primarily mechanical nonsurgical/surgical therapy for removal of the biofilm and calcified deposits from the implant surface .…”
Section: Biomaterial‐based Solutions As Future Perspectives To Prevenmentioning
confidence: 99%
“…However, depending on the bone loss extension, complete eradication of biofilm attached on dental implants is not easy, mainly in the apical region because peri‐implant pocket becomes deeper as the bone resorbs. Nowadays, focus on peri‐implantitis treatment requires primarily mechanical nonsurgical/surgical therapy for removal of the biofilm and calcified deposits from the implant surface . Although, those current therapies have been found to reduce probe depth and bleeding, from a clinical perspective, the evidences on their efficacy to treat peri‐implantitis are still limited.…”
Section: Biomaterial‐based Solutions As Future Perspectives To Prevenmentioning
confidence: 99%